Cytoprotective Effects of Dinitrosyl Iron Complexes on Viability of Human Fibroblasts and Cardiomyocytes - Natalia Pavlovna Akentieva; Natalia Pavlovna Akentieva; Natalia Pavlovna Akentieva; Natalia Alekseevna Sanina; Natalia Alekseevna Sanina; Artur Rasimovich Gizatullin; Natalia Ivanovna Shkondina; Tatyana Romanovna Prikhodchenko; Stanislav Ivanovich Shram; Nikolai Zhelev; Nikolai Zhelev; Sergei Michailovich Aldoshin; et al. (Frontiers Media S.A., 2019)
Nitric oxide (NO) is an important signaling molecule that plays a key role in maintaining vascular homeostasis. Dinitrosyl iron complexes (DNICs) generating NO are widely used to treat cardiovascular diseases. However, the involvement of DNICs in the metabolic processes of the cell, their protective properties in doxorubicin-induced toxicity remain to be clarified. Here, we found that novel class of mononuclear DNICs with functional sulfur-containing ligands enhanced the cell viability of human lung fibroblasts and rat cardiomyocytes. Moreover, DNICs demonstrated remarkable protection against doxorubicin-induced toxicity in fibroblasts and in rat cardiomyocytes (H9c2 cells). Data revealed that the DNICs compounds modulate the mitochondria function by decreasing the mitochondrial membrane potential (ΔΨm). Results of flow cytometry showed that DNICs were not affected the proliferation, growth of fibroblasts. In addition, this study showed that DNICs did not affect glutathione levels and the formation of reactive oxygen species in cells. Moreover, results indicated that DNICs maintained the ATP equilibrium in cells. Taken together, these findings show that DNICs have protective properties in vitro. It was further suggested that DNICs may be uncouplers of oxidative phosphorylation in mitochondria and protective mechanism is mainly provided by the leakage of excess charge through the mitochondrial membrane. It is assumed that the DNICs have the therapeutic potential for treating cardiovascular diseases and for decreasing of chemotherapy-induced cardiotoxicity in cancer survivors.